Find the values of m which make the following quadratic function a perfect square. x

^{2}+ 2(m + 1)x + m + 3-
**A.**

-1, 1 -
**B.**

-1, 2 -
**C.**

1, -2 -
**D.**

2, -2

##### Correct Answer: Option C

##### Explanation

x^{2} + 2(m + 1)x + m + 3 from (A + B)^{2} = a^{2} + 2AB + b^{2}

2B = (frac{2(m + 1)}{2}) = m + 1 …….(i)

Also B^{2} = m + 3……….(ii)

Subst. for B in equation ……….(iii)

= (m + 1)^{2} = m + 3 = m^{2} + 2m + 1 = m + 3

= m^{2} + 2m – m + 1 – 3 = 0

m^{2} + m – 2 = 0

(m + 2)(m – 1) = 0 or m – 1 = 0

m = -2 or 1